Tethering of Multi-Vesicular Bodies and the Tonoplast to the Plasma Membrane in Plants - Tao, Kai; Waletich, Justin R.; Wise, Hua; Arredondo, Felipe; Tyler, Brett M. (Frontiers in Plant Science, 2019)
Tethering of the plasma membrane (PM) and many organelles to the endoplasmic reticulum (ER) for communication and lipid exchange has been widely reported. However, despite growing interest in multi-vesicular bodies (MVBs) as possible sources of exosomes, tethering of MVBs to the PM has not been reported. Here we show that MVBs and the vacuolar membrane (tonoplast) could be tethered to the PM (PM-MVB/TP tethering) by artificial protein fusions or bimolecular fluorescence complementation (BiFC) complexes that contain a peripheral membrane protein that binds the PM and also a protein that binds MVBs or the tonoplast. PM-binding proteins capable of participating in PM-MVB/TP tethering included StRem1.3, BIK1, PBS1, CPK21, and the PtdIns(4)-binding proteins FAPP1 and Osh2. MVB/TP-binding proteins capable of participating in tethering included ARA6, ARA7, RHA1, RABG3f , and the PtdIns(3)P-binding proteins Vam7p and Hrs-2xFYVE. BiFC complexes or protein fusions capable of producing PM-MVB/TP tethering were visualized as large well-defined patches of fluorescence on the PM that could displace PM proteins such as AtFlotillin1 and also could displace cytoplasmic proteins such as soluble GFP. Furthermore, we identified paralogous ubiquitin E3 ligase proteins, SAUL1 (AtPUB44) and AtPUB43 that could produce PM-MVB/TP tethering. SAUL1 and AtPUB43 could produce tethering in uninfected tissue when paired with MVB-binding proteins or when their E3 ligase domain was deleted. When Nicotiana benthamiana leaf tissue was infected with Phytophthora capsici, full length SAUL1 and AtPUB43 localized in membrane patches consistent with PM-MVB/TP tethering. Our findings define new tools for studying PM-MVB/TP tethering and its possible role in plant defense.